2018
DOI: 10.1186/s41687-018-0052-7
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life burden of nonalcoholic steatohepatitis: a robust pragmatic literature review

Abstract: ObjectiveNonalcoholic steatohepatitis (NASH) is a form of chronic liver disease (CLD): patients have an increased risk of developing cirrhosis, liver failure, and complications (e.g. hepatocellular carcinoma). NASH has a high clinical burden, and likely impairs patients’ health-related quality of life (HRQoL), but there are currently no licensed therapies. The objective of this robust pragmatic literature review was to identify and describe recent studies on the HRQoL burden of NASH from the patient perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 27 publications
(108 reference statements)
1
51
0
2
Order By: Relevance
“…Although it could be argued that the differentiation and identification of symptoms between different comorbidities, i.e. liver disease and diabetes could be problematic 72 ; cirrhotic patients were reported as having worse physical health/functioning, 27 emotional health, mental health, 50 and were reported to experience more pain than non-cirrhotic patients with NAFLD. 39 Indeed, in 1 study aiming to determine the factors related to disability in cirrhotic outpatients, pain-related disability was reported to be 'nearly universal'.…”
Section: Discussionmentioning
confidence: 99%
“…Although it could be argued that the differentiation and identification of symptoms between different comorbidities, i.e. liver disease and diabetes could be problematic 72 ; cirrhotic patients were reported as having worse physical health/functioning, 27 emotional health, mental health, 50 and were reported to experience more pain than non-cirrhotic patients with NAFLD. 39 Indeed, in 1 study aiming to determine the factors related to disability in cirrhotic outpatients, pain-related disability was reported to be 'nearly universal'.…”
Section: Discussionmentioning
confidence: 99%
“…8,27,28 Previous research on the humanistic burden of NASH suggests that the physical burden of NASH, as opposed to the mental/emotional burden of NASH, is most prominent, with fatigue being a major aspect of reduced HRQoL. 9 Chawla et al 28 found that patients with NASH in the US, who were referred for evaluation of histology-proven NASH, exhibited reduced PCS scores, relative to pre-existing standardized general population norms. Similarly, Younossi et al 8 found that patients with NASH in the US and Canada, enrolled in a phase II open label study, exhibited reduced PCS scores (but not reduced MCS scores), relative to the standardized general population norms.…”
Section: Discussionmentioning
confidence: 99%
“…NASH may be associated with increased healthcare resource use (HRU), 7 impairment of work and non-work activities, 8 and diminished health-related quality of life (HRQoL). 9 Yet, further research is needed to comprehensively examine the humanistic and economic burden of NASH.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD/NASH induce non-specific and generally prevalent symptoms [36,37]; a large proportion of cases may be asymptomatic until patients develop decompensated cirrhosis [38][39][40]. Screening is therefore essential to ensure that patients, particularly those with advanced fibrosis (F3-F4), are identified and linked to care.…”
Section: Which Patient Populations Should Be Screened?mentioning
confidence: 99%